A crise econômica brasileira dos anos 1960: uma reconstrução do debate - Bugelli, Alexandre Hamilton (2008)
From 1962 the growth rates of the Gross Domestic Product start to decrease in regard to previous years, reaching the low mark of 0,6% in 1963. Otherwise, the inflation which in 1961 was about 51,6%, rose to 80% in 1962, reaching 93% in 1963. Those events attracted the interest of many economists who proposed several interpretations about this crisis, which became known as the brazilian economic crisis debate. This dissertation is about the recovery of the debate concerning the economic crisis of the beginning of the 60 s in Brazil and had as objective to organize and exam the analysis of the economists, who proposed to explain the crisis that occurred right after the country had experienced a deep industrial diversification process